MODERN APPROACHES TO TEACHING STUDENTS IN SMALL GROUPS AT THE DEPARTMENT OF NERVOUS DISEASES AND FOLK MEDICINE AT TSSI - Abdukodirov, Eldor Isroilovich; Kalanov, Asliddin Baxriddinovich; Abdukodirov, Doniyor Isroilovich (Researchparks Publishing, 2023)
The main goal of higher medical professional education is the preparation of qualified, competitive young professionals. To date, the development of medical students as professionals depends on many requirements, the main of which are initiative, the formation of personal independence, as well as the presence of a creative approach to education.